Enhancing motivation and learning in engineering courses: a challenge-based approach to teaching embedded systems - Lima, José (2023)
This paper addresses an approach to teaching embedded systems programming through a challenge-based competition involving robots. This pedagogical project distinguishes itself by incorporating international students from three international institutions through the Blended Intensive Program (BIP). The research findings indicate that this approach yields excellent results regarding student engagement and learning outcomes. The challenge-based program effectively promotes students’ creative problem-solving abilities by combining theoretical instruction with hands-on experience in a competitive setting.